2016
DOI: 10.15376/biores.11.1.2568-2582
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of UV-A on Dry Rice Straw Decomposition under Controlled Laboratory Conditions

Abstract: In arid and semi-arid areas, organic matter decomposition is stimulated by ultraviolet radiation. In this paper, the association between straw decomposition and UV-A exposure was evaluated. Oven-dried rice straw samples were chronically exposed to UV-A radiation and examined periodically for up to 90 days at room temperature. Scanning electron microscopy (SEM) showed that noticeable disintegration of the fiber structure occurred on the irradiated sample surface in comparison to the control. At the end of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…While the exclusion of solar UV radiation enhanced mass loss from leaf litter decomposing in the forest stands, the presence of UV-A radiation in the controlled environment tended to accelerate photodegradation. An increase in mass loss due to photodegradation in controlled environments has also been reported for rice and wheat straws exposed to enhanced UV-A [51] and UV-B radiation [52]. The effect of UV radiation did not transfer to decomposition under equivalent filters in forest stands, a distinction that would be consistent with any effect of sunlight photoinhibition on decomposers predominating over photochemical mineralization during the initial 6 months of decomposition following leaf fall.…”
Section: Discussionsupporting
confidence: 60%
“…While the exclusion of solar UV radiation enhanced mass loss from leaf litter decomposing in the forest stands, the presence of UV-A radiation in the controlled environment tended to accelerate photodegradation. An increase in mass loss due to photodegradation in controlled environments has also been reported for rice and wheat straws exposed to enhanced UV-A [51] and UV-B radiation [52]. The effect of UV radiation did not transfer to decomposition under equivalent filters in forest stands, a distinction that would be consistent with any effect of sunlight photoinhibition on decomposers predominating over photochemical mineralization during the initial 6 months of decomposition following leaf fall.…”
Section: Discussionsupporting
confidence: 60%
“…Bosco et al (2016) found additive effects of ultraviolet (UV) radiation and soil water on litter mass loss. Recent laboratory experiments have shown that the photodegradation of plant litter driven by UV radiation is important in influencing mass loss, nutrient release and the carbon balance in a broad range of terrestrial ecosystems (Austin et al, 2016;Li et al, 2016). It can be assumed that the loss of litter mass under the action of solar radiation (light and/or its thermal component) is at least partially related to the emission of VOCs, but at present it is difficult to draw definite conclusions in this regard due to the limited number of studies of this phenomenon.…”
Section: Abiotic Processesmentioning
confidence: 99%
“…The supernatant was separated from a 0.50-mm film filter after standing for 20 min. The liquid was analyzed by an elemental analyzer (Multi N/C 3100 Analyzer, Analytik-Jena Group, Jena, Germany) (Song et al 2011;Li et al 2016). The contents of potassium (K) and phosphorus (P) were recorded by flame photometric analysis and spectrophotometry, respectively (Song et al 2012).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…As a result, environmental microorganisms went into an apoptotic phase after day 100, and the straw decomposition rate gradually decreased until it was stable. Li et al (2016) exposed dry rice straw to increased UV-A irradiation and found that long-term radiation decreased the straw mass by 5%. The mass loss of 39.1% provides strong evidence that degradation was accelerated both by photodegradation and biodegradation.…”
Section: Mass Lossmentioning
confidence: 99%
See 1 more Smart Citation